APLIKASI MIKROORGANISME LOKAL (MOL) BONGGOL PISANG DALAM PEMBUATAN KOMPOS TANDAN KOSONG KELAPA SAWIT SEBAGAI PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) KELAS X BIOLOGI SMA - Amwa, Amita; ', Darmawati; ', Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the concentration of the most well Microorganisms Local (MOL) banana weevil in the composting of empty fruit bunches of oil palm. The research was conducted from February to June 2016. The results are used as development Worksheet Students (LKPD) Class X High School Biology. This research was done in 2 stages: stage composting using oil palm empty fruit bunches Local Microorganisms (MOL) banana weevil in the Laboratory of Biology of Natural PMIPA using the RAL consisting of 4 treatments and 3 replications. The development phase Worksheet Students (LKPD) development model ADDIE ((Analyze, Design, Development, Implementation and Evaluation), composting of empty fruit bunches of oil palm consists of preparation of tools and materials to be used, composting, observation of the composting process and stages completion. the parameters in this study is the C / N ratio of compost, the content of N, P and K compost as well as temperature, humidity and pH. The result showed that the treatment with a concentration of 4 ml MOL banana weevil is the best concentration in composting palm empty fruit bunches of oil. The results of the study and then developed as Worksheet Students (LKPD) class X Biology.Keywords : Microorganisms Local(MOL), Banana weevil, Empty fruit bunches of oil palm, development learners worksheet,